Severe Rhabdomyolysis Associated with Simvastatin and Role of Ciprofloxacin and Amlodipine Coadministration - Nicolas De Schryver; Xavier Wittebole; Peter Van den Bergh; Vincent Haufroid; Eric Goffin; Philippe Hantson (Case Reports in Nephrology)
Simvastatin is among the most commonly used prescription medications for cholesterol reduction and the most common statin-related adverse drug reaction is skeletal muscle toxicity. Multiple factors have been shown to influence simvastatin-induced myopathy. In addition to age, gender, ethnicity, genetic predisposition, and dose, drug-drug interactions play a major role. This is particularly true for drugs that are extensively metabolized by cytochrome P450 (CYP)3A4. We describe a particularly severe case of rhabdomyolysis after the introduction of ciprofloxacin, a weak CYP3A4 inhibitor, in a patient who previously tolerated the simvastatin-amlodipine combination.